Curcumin Analog Pentagamaboronon-0-Sorbitol Inhibits Cell Migration Activity of Triple Negative Breast Cancer Cell Line - Ratna Dwi Ramadani; Rohmad Yudi Utomo; Adam Hermawan; Edy Meiyanto (Indonesian Journal of Cancer Chemoprevention, 2018)
Mortality in cancer is primarily due to failure of metastasis prevention. One strategy to target the cancerous cell is Boron Neutron Captured Therapy which showed high affinity toward cancer cells and reported to have anti-proliferative as well as antimetastatic activities. Cancer Chemoprevention Research Center Faculty of Pharmacy Universitas Gadjah Mada, has developed boron-containing substance namely pentagamaboronon-0 (PGB-0) which is known to exhibit anticancer activity towards breast cancer cell. The purposes of this research are focused to explore the anti-migratory activities of PGB-0-So against triple negative breast cancer cell. The MTT cytotoxicity assay of PGB-0-So against 4T1 breast cancer cell line were found to exert potential effect in dose-dependent manner with IC50 values of 39 μM. The study of cell migration inhibition using in vitro wound healing assays and gelatin zymography on highly metastasis breast cancer cell line 4T1, following the treatment of sub IC50 doses of PGB-0-So complex slightly inhibited cell migration through the inhibition of matrix metalloproteinase-9 expression. These findings suggest that PGB-0-So is potential as an anticancer agent.Keywords : curcumin analogue, PGB-0-So, 4T1 Cells, migration, MMP-9